Hubungan Perilaku Sleep hygiene dengan Insomnia pada Lansia Di Puskesmas Cibeber Kota Cimahi - Lina Safarina; Alpina Damayanti (Yayasan Healing and Healthcare Education, 2026)
Insomnia is the most common sleep disorder experienced by older adults and may negatively affect their health and quality of life. Sleep hygiene refers to behavioral and environmental practices that promote good sleep quality through proper pre-sleep activities and a conducive sleep environment. The prevalence of insomnia among older adults in Indonesia is relatively high, including in West Java Province and the Cibeber sub-district. This study aimed to determine the relationship between sleep hygiene behavior and insomnia among older adults at the RW 02 Integrated Health Post (Posbindu) in the working area of Cibeber Public Health Center, Cimahi City, in 2025. This study employed a quantitative method with a cross-sectional design. Purposive sampling was used to recruit 114 respondents. The instruments included the Sleep Hygiene Index (SHI) and the Insomnia Severity Index (ISI). Data were analyzed using frequency distribution for univariate analysis and Spearman Rank correlation test for bivariate analysis with a significance level of 0.05. The results showed a significant relationship between sleep hygiene behavior and insomnia among older adults (p = 0.001; r = 0.868), indicating a very strong and positive correlation. Proper implementation of sleep hygiene practices may reduce insomnia levels in older adults. Therefore, education and intervention programs focusing on sleep hygiene should be strengthened in elderly health services.